Two Piscan Aeromonas Vaccine Strategies - Shnawa, Ibrahim M S; Alsady, Bshar E Ah; Jalel, Sermad (British Journal of Healthcare and Medical Research, 2019)
A piscan Aeromonas ulcerative infection episode was revisiting Babylon province, IRAQ at 2018 following to that of 2015.. Two Aeromonas hydrophila vaccines are being developed and delivered in two strategies for common carp fish . First the heterologous prime-boost and second the homologous prime boost in combination with Alhagi Root Adjuvant[HRA] 3.5 gm/kg ration. These strategies were as, heat killed[AHKV] prime-live[AHLV] and HPA-AHLV prime-AHLV boost with immunogenicity group, infection group and sham controls in an aquaculture system provided with an optimal culture conditions. Both of Heterologous and homologous prime boost proved to be immunogenic as determined from A. hydrophila specific serum agglutinins which was of up to titre of 1280 and 2560 with survival rate of 100% and duration of immunity to three to six weeks post to the initial vaccination for the survived fish. The developmental evaluation criteria of both of vaccines were matching to that of other workers .In this aquaculture system. preconditioning with HPA for 21 days before vaccination was found comparable to vaccination with dead prime vaccine in the sense of; immunogenicity and survival rate and safety .Wider application of these two vaccination strategies in the natural conditions of commercial fish farming ponds is being an inherent need for confirmation of the present findings